1997
DOI: 10.1074/jbc.272.27.16725
|View full text |Cite
|
Sign up to set email alerts
|

Activation of c-Jun N-terminal Kinase Antagonizes an Anti-apoptotic Action of Bcl-2

Abstract: Bcl-2 is an intracellular membrane-associated protein that prevents cell death induced by a variety of apoptotic stimuli. A mechanism by which Bcl-2 exerts an anti-cell death effect is, however, not fully understood. In the present study, Bcl-2 suppressed cell death of N18TG neuroglioma cells caused by various apoptotic stresses, including etoposide, staurosporine, anisomycin, and ultraviolet irradiation. Concomitantly, Bcl-2 disrupted a signaling cascade to the c-Jun N-terminal kinase activation induced by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
84
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 112 publications
(87 citation statements)
references
References 25 publications
3
84
0
Order By: Relevance
“…Interestingly, it has recently been shown that overexpression of SAPK/JNK antagonized the anti-apoptotic effect of Bcl-2, presumably due to sustained activation of SAPK/JNK (Park et al, 1997). Pro-apoptotic Bcl-2 family members, such as Bax, can antagonize the effects exerted by the anti-apoptotic members.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it has recently been shown that overexpression of SAPK/JNK antagonized the anti-apoptotic effect of Bcl-2, presumably due to sustained activation of SAPK/JNK (Park et al, 1997). Pro-apoptotic Bcl-2 family members, such as Bax, can antagonize the effects exerted by the anti-apoptotic members.…”
Section: Discussionmentioning
confidence: 99%
“…Actually, JNK induces the expression of BH3-only proteins: Hrk and Bim (Harris and Johnson, 2001). Jun N-terminal kinase also phosphorylates Bcl-2 family members and promotes pro-apoptotic Bax activity (Kim et al, 2006), and inhibits various anti-apoptotic Bcl-2 family members, including Bcl-2, Bcl-x L and Mcl-1 (Ito et al, 1997;Park et al, 1997). In addition, JNK indirectly determines the activation of Bax through its regulation of 14-3-3 (Tsuruta et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…35 Correspondingly, activation of the JNK/SAPK pathway in combination with a repressed growth factor activated ERK-cascade has been shown to be required for apoptosis and a balance between JNK/SAPK and ERK has been found to be critical in affecting the apoptotic outcome. 30 In addition, JNK/SAPK activity may also occur independently of death receptor triggering as described in response to cellular stress.…”
Section: Discussionmentioning
confidence: 99%